2020
DOI: 10.1002/jbt.22595
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and carcinoma: Two facets of dysfunctional cholesterol homeostasis

Abstract: Although cholesterol is an essential and necessary component for biological systems; inappropriate accumulation of cholesterol in blood vessels and intracellular territory is also detrimental to living things. On one hand, cholesterol is the acting precursor of many metabolic regulators, a component of the structural veracity and scaffold fluidity of biomembranes, an insulator of electrical transmission in nerves and many more; on the other hand, its deposition in blood vessels induces atherosclerotic plaque a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…AS is more common in middle-aged and elderly people over 40 years old, and progresses faster after 49 years old. The incidence of AS in men is higher than that in women before menopause and the incidence is similar in both sexes after menopause [ 3 , 4 ]. The exact cause of AS is currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…AS is more common in middle-aged and elderly people over 40 years old, and progresses faster after 49 years old. The incidence of AS in men is higher than that in women before menopause and the incidence is similar in both sexes after menopause [ 3 , 4 ]. The exact cause of AS is currently not known.…”
Section: Introductionmentioning
confidence: 99%
“…4 In fact, evidence has shown that high cholesterol levels are linked to the risk of atherosclerotic cardiovascular events, due to the accumulation of cholesterol in atherosclerotic plaques. 5,6 Cholesterol, a key molecule in this entire process, plays a significant role in a variety of homeostatic systems. 7 Most mammalian cells can acquire cholesterol from two independent sources.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is thought, at least in part, to be an inflammatory mechanism caused by free radicals [8,9]. In addition to this, B[a]P was shown to stimulate formation of ROS and promote the progression of atherosclerosis [10,11]. Mechanisms that are redox-sensitive are used to monitor various inflammatory genes and related transcription factors.…”
Section: Introductionmentioning
confidence: 99%